POLITICAL VIOLENCE AND THE SUSTAINABILITY OF NIGERIAN DEMOCRACY - Nkwede, Joseph Okwesili; ALOYSIUS S., IBEOGU,; Mwambene, Eric (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
This paper titled Political Violence and The Sustainability of Nigerian Democracy seeks to establish the causes of political violence in Nigerian democratic experiment and possibly suggest how to surmount the pathologies with a view to ensuring the survival of the nations fledgling democracy. The study adopted elite theory as a theoretical framework of analysis. The study established that greed, struggle for supremacy between godfathers and godsons have often led to political violence in the countrys party system. The implication of the study is that if the above factors are not assuaged, the polity will continue to elect and nominate mediocre to occupy positions of responsibilities. Similarly, the country polity will keep witnessing wanton destruction of lives and properties. The study therefore recommended that the existing sentiments and parochial cleavages such as ethnicity and religion should not be a pre-requisite when it comes to attracting the suitable qualified candidates for public and political offices.